2008
DOI: 10.1002/ejic.200800448
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐Containing Ionic Liquids from N‐Alkylpyrrolidine and N‐Methylpiperidine and Fluorinated Acetylacetones: Low Melting Points and Low Viscosities

Abstract: A family of new fluorine‐containing ionic liquids (3–14) was synthesized in high yield by the reaction of N‐alkylpyrrolidine, N‐methylpiperidine and fluorinated 1,3‐diketones: 1,1,1,5,5,5‐hexafluoroacetylacetone, 1,1,1‐trifluoro‐2,4‐pentanedione and 4,4,4‐trifluoro‐1‐phenyl‐1,3‐butanedione. Their properties, such as the phase‐transition temperature, density, and viscosity, were determined. Most of them show relatively low melting points and low viscosities. The influence of fluorinated 1,3‐diketonate anions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…65,71 number and strength of interactions and/or coordination, 66,67,69 which is dependent on the level of delocalisation. 68 the conformational flexibility-a higher flexibility yields a lower melting point. 71 packing efficiency-less efficient packing results in a lower melting point.…”
Section: Ionic Substitution And/or Modificationmentioning
confidence: 99%
“…65,71 number and strength of interactions and/or coordination, 66,67,69 which is dependent on the level of delocalisation. 68 the conformational flexibility-a higher flexibility yields a lower melting point. 71 packing efficiency-less efficient packing results in a lower melting point.…”
Section: Ionic Substitution And/or Modificationmentioning
confidence: 99%
“…However, the synthesis of this IL is quite involved, entailing a multistep process including anion metathesis of an IL halide salt and ammonium hfca [95]. Alternatively, Gupta et al [96,97] and Li et al [98] reported a method for synthesizing PILs utilizing β-diketones and tertiary amines, entailing a simple single pot neutralization reaction. Yet, none of the ILs synthesized by this method have been applied to extraction processes.…”
Section: +mentioning
confidence: 97%
“…So the extraction mechanism and structure-activity relationships of ammonium-Bif-ILEs with REs(III) are much more complex than for traditional organic extractants. Several 1,3-diketonate extractants, including 2-thenoyltrifluoro-acetone (HTTA), 1,1,1-trifluoro-2,4-pentanedione (HTFA), and benzoyltrifluoroacetone (HBTA), are widely used for RE(III) extraction with various synergistic agents [16][17][18] owing to weak coordination between the 1,3-diketonate moiety and REs(III). The quaternary ammonium salt [A336]Cl is extensively used as a synergistic agent, often in combination with HTTA, for synergistic extraction of trivalent lanthanides [2,3], which has been found to be considerably enhanced relative to [A336]Cl salts or HTTA alone.…”
Section: Introductionmentioning
confidence: 99%